2005
DOI: 10.3201/eid1111.050367
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistantStaphylococcus aureusin Taiwan

Abstract: We found a virulent closely related clone (Panton-Valentine leukocidin–positive, SCCmec V:ST59) of methicillin-resistant Staphylococcus aureus in inpatients and outpatients in Taiwan. The isolates were found mostly in wounds but were also detected in blood, ear, respiratory, and other specimens; all were susceptible to ciprofloxacin, gentamicin, and trimethoprim-sulfamethoxazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 14 publications
4
28
1
Order By: Relevance
“…However, multiple non-b-lactam antimicrobial resistance phenotypes were found in our SCCmec type V isolates, and all of these strains were resistant to at least two, to a maximum of four, non-b-lactam drugs. These data are in line with reports from other localities (Chen et al, 2005;Coombs et al, 2006). In addition, three of our strains were resistant to ciprofloxacin, and susceptibility to fluoroquinolones as a marker for recognizing putative CA-pvlpositive MRSA strains may be unreliable (Millar et al, 2007).…”
Section: Jmm Correspondencesupporting
confidence: 91%
See 1 more Smart Citation
“…However, multiple non-b-lactam antimicrobial resistance phenotypes were found in our SCCmec type V isolates, and all of these strains were resistant to at least two, to a maximum of four, non-b-lactam drugs. These data are in line with reports from other localities (Chen et al, 2005;Coombs et al, 2006). In addition, three of our strains were resistant to ciprofloxacin, and susceptibility to fluoroquinolones as a marker for recognizing putative CA-pvlpositive MRSA strains may be unreliable (Millar et al, 2007).…”
Section: Jmm Correspondencesupporting
confidence: 91%
“…Since the 1990s, community-associated (CA)-MRSA infections have shown a steady increase, and are becoming a significant public-health concern. PVLpositive MRSA isolates have been shown to have distinct genetic backgrounds in different areas, for instance, multilocus sequence typing (MLST) types ST80, ST8 and ST59 were found in the major clones in Europe, USA and Taiwan, respectively (Vandenesch et al, 2003;Tristan et al, 2007;Chen et al, 2005).…”
Section: Jmm Correspondencementioning
confidence: 99%
“…However, the patients in the current study were from the community, which might explain the heterogeneity of spa type and pulsotype. As previous studies in Taiwan have revealed [21], isolates with different SCCmec genotypes belonged to specific sequence types or spa types. ST59, a community clone in Taiwan often carrying SCCmec IV/V, has replaced the traditional HCA clones, but it is less commonly associated with the SCCmec II/III genotypes [8,15,22].…”
Section: Discussionmentioning
confidence: 96%
“…Seventeen clinical MRSA strains from our previous study (5,7) were chosen for mecA gene sequencing, including one SCCmec II isolate, two SCCmec III isolates, six SCCmec IV isolates, and eight SCCmec V isolates (see Table 3). Additional SCCmec type IV and V clinical isolates were included because they exhibited more diverse oxacillin MIC values on the basis of Etest results.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%